The complete mitogenome of Bagrid catfish Chrysichthys nigrodigitatus (Siluriformes: Claroteidae) - Nack-Keun Kim; Fantong Zealous Gietbong; Sapto Andriyono; Ah Ran Kim; Hyun-Woo Kim (Mitochondrial DNA. Part B. Resources, 2018)
We here report the complete mitochondrial genome of Chrysichthys nigrodigitatus, which is 16,514 bp in length. Mitogenome of C. nigrodigitatus showed the conserved 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and two noncoding regions including the light-strand replication origin (OL) and a putative control region (CR). All tRNA genes were predicted to fold into the typical cloverleaf secondary structures with the typical base-pairing except for tRNA-Ser(AGC). Phylogenetic analysis with currently known complete mitogenome sequences in Siluriformes showed that C. nigrodigitatus is most closely related to Auchenoglanis occidentalis forming a family Claroteidae cluster.